Perkembangan Padepokan Seni Sunda â€œKarang Kamulyanâ€ di Kampung Karang Pawitan Desa Pakutandang Kec. Ciparay Kab. Bandung Tahun (1997-2021) - Hasna Nafa Nasihah (UIN Sunan Gunung Djati Bandung, 2025)
The Karang Kamulyan Art Padepokan was founded by a husband and wife, namely Ugan Rahayu and Neni Hayati and Asep Setia Pujanegara which aims to preserve Sundanese arts. The development of the Karang Kamulyan hermitage began in 1997 when it only had makeshift gamelan instrument until in 2014 it received financial assistance from the government for artistict intstrument at the Karang Kamulyan hermitage. The Karang Kamulyan Art Padepokan is now well known by the public and is often invited to various events not only in the Bandung district but in several regions in Indonesia. Writing this article aims to find out the history of the establishment of the Karang Kamulyan Art Hermitage and its development. The writing of this article uses historical research methods which have 4 stages, namely, heuristics, critism, interpretation, and historiography. The results of the analysis show that the development of the Karang Kamulyan hermitage was carries out in various ways, so that the Karang Kamulyan art hermitage can still exist today.